Assessing contemporary parenting dimensions : development and psychometric investigation of the parenting behaviours and dimensions questionnaire - Reid, Carly Ae Yeong (Curtin University, 2012)
While a substantial amount of research has been conducted on parenting and its effects on child development, there is a significant lack of agreement over the key dimensions of parenting and the assessment of parenting behaviour. Most parenting dimensions that have been examined in previous studies can be subsumed under the themes of parenting warmth, behavioural control, and psychological control; however, there are many other dimensions discussed in the literature that may be important to the practices of contemporary parents. In addition, the assessment of parenting has been problematic due to theoretical disagreement, concerns over generalisability, and problems with the developmental methods and psychometric properties of current measures of parenting. Therefore, the aims of this research were to develop a comprehensive and psychometrically sound self-report measure of parenting for use with parents of preadolescent children, and to use this empirical scale development process to identify the core dimensions of contemporary parenting practices. The final aim of the study was to use the newly developed Parenting Behaviours and Dimensions Questionnaire (PBDQ) to address some of the questions in the literature relating to the generalisability and universality of parenting theory and assessment across various parenting subgroups. The research employed a mixed-method design, combining previous literature and assessment items with qualitative parent feedback and quantitative scale development, validation, and practical utility assessment procedures.In Phase One of this research, the initial item pool (N = 288) was generated, which were based on items from six widely used parenting measures, as well as a list of items generated by the researcher on parental responsiveness, intrusiveness, and overprotection, based on previous literature. After items were reviewed for redundancies (N = 210), a sample of 16 parents of children aged 3 to 12 years provided written feedback on the item pool, and a further sample of 15 parents participated in one of three focus groups discussing the items as well as important parenting themes that were not covered in the item pool. Verbatim item feedback from both phases as well as content analysis of the focus group transcripts resulted in the elimination of 115 items, while 29 items were reworded and 21 items were added, yielding a total of 116 items in the final item pool assessing a range of parenting behaviours.In Phase Two, a community sample of 846 parents of children aged 3-12 years completed an online survey of the items in the final item pool. Exploratory factor analysis conducted on a randomly selected sample of 580 of these parents yielded a six factor solution, including dimensions of Emotional Warmth, Punitive Discipline, Responsiveness, Discipline Inconsistency, Democratic Discipline, and Anxious Intrusiveness. A confirmatory factor analysis conducted on the remaining 266 parents supported a higher order five factor solution, with the Anxious Intrusiveness factor excluded from the model. The final Parenting Behaviours and Dimensions Questionnaire included 27 items, and Cronbach’s alphas were found to be acceptable to excellent.A community sample of 105 parents completed an online test-retest study in Phase Three, and results supported the relative stability of the PBDQ over a two and four week period. This sample was combined with a further sample of 58 parents recruited for the Animal Fun Project at Curtin University (Piek et al., 2010). Validity analyses comparing the PBDQ to the Strengths and Difficulties Questionnaire (Goodman, 1997) subscale scores and the Social Skills Rating System (Gresham & Elliot, 1990) subscale scores were generally in the expected direction. In general, better childhood outcomes were associated with lower levels of parental punitive discipline, discipline inconsistency, and anxious intrusiveness, and higher levels of parent emotional warmth, responsiveness, and democratic discipline.Phase Four utilised the data from Phase Two to assess the utility and generalisability of the PBDQ, and results suggested that there was very little variability in PBDQ scores across parent gender, child gender, and individualistic versus collectivist cultural groups, with some differences in PBDQ variability between primary and non-primary caregivers. In addition, the factorial validity for the PBDQ across parents of male and female children was confirmed, and there were no significant differences in PBDQ scores across parent gender x caregiver status, or child gender. Finally, significant variance in PBDQ scores was accounted for by important demographic variables in the regression analyses, but effect sizes were small. Taken together, these results provide support for the utility of the PBDQ and the underlying factor structure, and the universality of the dimensions assessed across a range of demographic variables.The overall findings of this project provide support for the psychometric properties, universality, and practical utility of the PBDQ, which was developed to address the theoretical, methodological, and psychometric limitations of previous measures. The five dimensions which are described in the PBDQ appear to combine a number of different parenting concepts that have been identified in the literature, providing some clarity to the definition of key parenting dimensions. This measure will allow for the comprehensive and consistent assessment of parenting, and the development of alternative assessment systems based on these core dimensions to assist in future research and clinical practice.